Islamic Education Management based on Religious Moderation in the Industrial Revolution 4.0 Era - Khotijah Khotijah; Dedi Wahyudi; Nawang Wulandari; Faisal Mahmoud Adam Ibrahim (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2022)
This paper aims to provide views on efforts to ground religious moderation education, primarily through managing Islamic education based on religious moderation in the 4.0 era. This study is a type of qualitative research with a library research approach. The data collection carried out in this article was obtained through reviewing or exploring various literature studies. The results show that an increase in Islamic education management can be done through technology and an increase in human resources who are aware of science and technology accompanied by a balance of the quality of faith and piety to have a solid spiritual, intellectual and moral foundation. In addition, the reform of the Islamic education system is in the aspects of paradigms, concepts, frameworks, and evaluations. The conclusion is that it is necessary to improve the management of Islamic education so that it develops better based on religious moderation, which can be used as a spiritual, moral, and intellectual laboratory.